Academic Control, Resilience, and Self-Directed Learning: A Cross-Sectional Study - Ahmmed, Badhon; Chaudhary, Aman Ullah; Nasrin , Sharmin (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
This study aims to investigate the relationships between self-directed learning (SDL), perceived academic control, and academic resilience among university students. The primary objective is to determine how perceived academic control and academic resilience predict SDL. A cross-sectional study design was employed with a sample size of 209 undergraduate students, selected based on the Morgan and Krejcie table. Participants were assessed using the Self-Directed Learning Readiness Scale (SDLRS), the Academic Control Scale (ACS), and the Academic Resilience Scale (ARS-30). Data analysis was performed using SPSS version 27, employing Pearson correlation to explore relationships between variables and linear regression to determine predictive power. Descriptive statistics revealed mean scores of 3.75 (SD = 0.65) for SDL, 3.50 (SD = 0.70) for perceived academic control, and 3.80 (SD = 0.68) for academic resilience. Pearson correlation analysis showed significant positive relationships between SDL and perceived academic control (r = 0.45, p < 0.001) and between SDL and academic resilience (r = 0.55, p < 0.001). The regression model was significant (F(2, 206) = 62.80, p < 0.001), with an R² of 0.38, indicating that perceived academic control and academic resilience together explain 38% of the variance in SDL. Both perceived academic control (B = 0.30, β = 0.32, p < 0.001) and academic resilience (B = 0.42, β = 0.45, p < 0.001) were significant predictors of SDL. The findings suggest that perceived academic control and academic resilience are significant predictors of self-directed learning among university students. Enhancing these attributes could foster better self-directed learning capabilities, contributing to improved academic outcomes. Educational interventions that boost students’ perception of control and resilience are recommended to support autonomous learning.